Occurance, Distribution and Bioremediation of Endocrine Disrupting Chemicals in Coastal Sediments from Macao SAR, China - Lebel, Alexandre (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph

Grammar of Macao Creole Portuguese with Typological and Semiotic Considerations - Lebel, Alexandre (University of Saint Joseph, 2021)
Macao Creole Portuguese (MacCP) is a critically endangered language spoken in Southeastern China. The formation of MacCP is attributed to the speakers of Portuguese-based creole languages in Asia (Asian CPs), especially Papia Kristang, the Malayo-Portuguese of Malacca (MalCP). Since the 19th century, MacCP has been traditionally classified as Sino-Portuguese, but comparative methods incited some authors to treat MacCP within the Malayo-Portuguese group. In Macao, the Malaccan origin of MacCP, known as Patúa or Maquista, is generally underestimated or misunderstood by the local population, including the Macanese/Maquista community. The main goal of this research is to clarify the origin of MacCP from a typological perspective on grammatical features. Secondly, while considering a possible revitalization of Maquista, the research should assess the significance of the Malayo- and Sino-Portuguese classifications in popular narratives and relate the language to current practices. The grammar of MacCP emerged from the complex linguistic ecology of the Portuguese colonial expansion in Asia. The documentation of Asian CPs allows us to sketch possible scenarios that explain the formation of MacCP according to linguistic, historical and social factors. A digital corpus of MacCP containing archive documents, contemporary literature, and oral transcriptions was assembled in order to produce a systematic review of 130 grammatical features, as defined in the Atlas of Pidgin and Creole Language Structures Online (APiCS Online – Michaelis et al. [eds] 2013). MacCP and MalCP share certain features that are not found in South Asian CPs, such as the in situ position of interrogative words, the reduplication for nominal plural, the form of reciprocal constructions, and the verb serialization of motion constructions, thus pointing to the Malayo-Portuguese origin. At the same time, other features suggest a certain influence from Sinitic languages, mainly Cantonese and Hokkien, such as the convergence between the genitive, adjective and relative clause constructions, the double-object construction, the verb-neg-verb polar question, the copular focus construction, the reduplication inducing a change of word class or semantics, and the use of certain deontic, imperative, and prohibitive verbal markers. The comparative analysis of the grammars of MacCP, MalCP and other Asian CPs can be represented quantitatively by the means of a phylogenetic network (SplitsTree4 – Huson & Bryant 2006). The results clearly indicate that, from a structural perspective, MacCP belongs to the Malayo-Portuguese group and the presence of Sinitic elements did not affect the core of the grammar. In fact, MacCP and MalCP appear to be more similar to each other than to the former Malayo-Portuguese of Batavia. However, the Malayo-Portuguese classification of MacCP does not resonate with the Macanese community. By contrast, the Sino-Portuguese classification translates current linguistic, social and semiotic practices. A socio-semiotic survey among the millennial generation of Macanese and the consideration of themes and motifs in Maquista literature indicates that the revitalization of Maquista simultaneously implies, in their views, the preservation of the Cantonese and Portuguese heritage
Keywords: Thesis and Dissertations PhD in Education (D-SE); University of Saint Joseph